Early Mobilization Training Education for Sectio Caesarea Patients - Desy Rahayu; Susanto, Amin; Netra Wirakhmi, Ikit (Java Nursing Journal, 2024)
Background: The global rise in caesarean section (C-section) rates, particularly in Asia where the incidence stands at 19.5%, underscores the need for effective post-operative care strategies. Early mobilization is critical for post-C-section recovery, as it enhances patient mobility, reduces complications, and promotes overall health. Purpose: This study aims to assess the impact of early mobilization education on post-C-section patients' knowledge. Methods: This community service initiative, conducted at the Albarokah Room of Purwokerto Islamic Hospital, targeted 30 post-C-section maternal patients. The educational intervention was delivered using audiovisual media and the caramah method. Knowledge levels were assessed using a pre- and post-intervention questionnaire, which evaluated understanding of early mobilization, its benefits, contraindications, and procedural stages. Findings: Prior to the educational intervention, participants' knowledge was predominantly categorized as poor, with 40% (12 participants) scoring in this range. Post-education assessment revealed a significant improvement, with 100% (30 participants) achieving a good knowledge level regarding early mobilization. Conclusions: The implementation of early mobilization education through audiovisual media markedly improved participants' knowledge about early mobilization post-C-section. This study demonstrates that structured educational interventions can effectively enhance patient understanding and potentially improve post-operative outcomes. Further research is warranted to explore long-term effects on recovery and health